To determine the crushing strength and drop strength of green iron ore pellets by varying % of bentonite (1, 2, 3, 4%) additives keeping 12% moisture and to determine the crushing strength and drop strength of green iron ore pellets by varying % of water addition (8, 9, 10, 12, 14 %) keeping 2%Na-based bentonite - Rao, Lakkoju Sankara (Main Library, IIT (BHU), Varanasi, 2022)
PART 1 Introduction PART 2 Pellet Preparation PART 3 Drop Strength& Crushing Strength PART 4 Crushing Strength & Drop Strength PART 5 Crushing Strength (41:18- 50:00)